Intellectual Capital Terhadap Financial Leverage: Risiko Perusahaan Dan Profitabilitas - Annisa Maulida Harahap; Isfenti Sadalia; Nisrul Irawati (Owner : Riset dan Jurnal Akuntansi, 2023)
Data from IDX Statistics 2020 state that the financial sector, especially banking sector has market capitalization rate at 33% of all the total market capitalization in Indonesia. The rate of the market capitalization of banking sector shows that bank sector has a big role in economics of country. This study analyzes the effect of intellectual capital on financial leverage with firm risk and profitability as mediating variables of conventional commercial foreign exchange banks in Indonesia Stock Exchange. The data collection method for this research is a literature study and documentation method, that is the financial statements of conventional commercial foreign exchange banks in the Indonesia Stock Exchange that collecting from 2016 to 2020. There are 29 populations who are all sampled. This research method is descriptive data and Partial Least Square (PLS). The results of the study show that only VACA, VAIC indicator, shaping the value of intellectual capital. Intellectual capital has a negative and significant effect on financial leverage. Intellectual capital has a positive and significant effect on firm risk. intellectual capital has a positive and significant effect on profitability. Firm risk and profitability are not able to mediate the influence of intellectual capital on financial leverage. Firm risk has a positive and insignificant effect on financial leverage. Profitability has a positive and significant effect on financial leverage.